Factors Influencing Mood Disorders and Health Related Quality of Life in Adults With Glioma: A Longitudinal Study - Leonetti, Antonella; Puglisi, Guglielmo; Rossi, Marco; Viganò, Luca; Conti Nibali, Marco; Gay, Lorenzo; Sciortino, Tommaso; Howells, Henrietta; Fornia, Luca; Riva, Marco; Cerri, Gabriella; Bello, Lorenzo (Frontiers in Oncology, 2021)
Objective: At present, it is not clear whether Mood Disorders (MD) and poor Health Related Quality of Life (HRQoL) in the glioma population correlate with features of the tumor, or rather with secondary symptoms associated with treatment. The aim of this study was to assess the prevalence of MD and decline in HRQoL in glioma patients, and to determine the main factors associated with these two variables. Methods 80 patients affected by lower-grade gliomas (LGGs) and 65 affected by high-grade gliomas (HGGs) were evaluated, from admission up to 12 months after surgery, for MD, HRQoL, clinical characteristics, and cognitive functions. Independent factors associated with MD and low HRQoL were identified by using bivariate analysis. Results. Data showed that prevalence of low HRQoL was comparable in both groups during all the time points assessed (pre, 1, 3, 6 and 12 months after surgery). In contrast at 6 months following surgery , HGGs showed a higher prevalence of MD compared to LGGs; . Bivariate analysis revealed that factors associated with MD and HRQoL in LGGs and HGGs were different over the course of the disease. In LGGs, from the pre-operative period to one year post surgery, MD and low HRQOL were associated with the occurrence of cognitive deficits and, from the third month after surgery onward, they were also associated with the effect exerted by adjuvant treatments. In HGGs, MD were associated with cognitive deficits at 3 and 6 months after surgery, along with older age (65-75 years); HRQoL, in its Physical component in particular, was associated with older age only from 6 months after surgery. Conclusion. Factors associated with MD and low HRQoL were different in LGGs and HGGs over the course of the disease. In LGGs the effect of adjuvant treatments was prominent in determining the prevalence of both MD and poor HRQoL from the third month after surgery onward. In HGGs, MD and HRQoL were associated with age, at 3 and 6 months after surgery. In both, the occurrence of cognitive deficits was significantly associated with MD.